Work and Extra-Work Correlates of Life and Job Satisfaction - Near, Janet P.; Rice, Robert W.; Hunt, Raymond G. (Academy of Management Journal, 1978)
A probability sample survey (n = 1,041) explored the relationship of both work-related and extra-workplace variables to four subjective quality of life measures: life satisfaction, life satisfaction over time, job satisfaction, and evaluation of health. The interrelationships among these four measures were also examined. A conceptual model relating job satisfaction to life satisfaction was offered.